Analysis of multiple Brachyspira hyodysenteriae genomes confirms that the species is relatively conserved but has potentially important strain variation - Black, M.; Moolhuijzen, Paula; Barrero, R.; La, T.; Phillips, N.; Hampson, D.; Herbst, W.; Barth, S.; Bellgard, M. (Public Library of Science, 2015)
The intestinal spirochete Brachyspira hyodysenteriae is an important pathogen in swine, causing mucohemorrhagic colitis in a disease known as swine dysentery. Based on the detection of significant linkage disequilibrium in multilocus sequence data, the species is considered to be clonal. An analysis of the genome sequence of Western Australian B. hyodysenteriae strain WA1 has been published, and in the current study 19 further strains from countries around the world were sequenced with Illumina technology. The genomes were assembled and aligned to over 97.5% of the reference WA1 genome at a percentage sequence identity better than 80%. Strain regions not aligned to the reference ranged between 0.2 and 2.5%. Clustering of the strain genes found on average 2,354 (88%) core genes, 255 (8.6%) ancillary genes and 77 (2.9%) unique genes per strain. Depending on the strain the proportion of genes with 100% sequence identity to WA1 ranged from 85% to 20%. The result is a global comparative genomic analysis of B. hyodysenteriae genomes revealing potential differential phenotypic markers for numerous strains. Despite the differences found, the genomes were less varied than those of the related pathogenic species Brachyspira pilosicoli, and the analysis supports the clonal nature of the species. From this study, a public genome resource has been created that will serve as a repository for further genetic and phenotypic studies of these important porcine bacteria. This is the first intra-species B. hyodysenteriae comparative genomic analysis.